Spaniards Exiled Poets in Dominican Republic (1939-1945) (2023)
The Spanish Civil War and Franco’s regime caused the exile of a large group of intellectuals. In Dominican Republic, one of the host countries, literature but especially poetry was used to demonstrate the causes and results of the diaspora caused by the republican defeat. We analyzed the work of some of the most prominent and representative poets as a reflection of an unaccepted reality that went deep into Dominican’s culture. Methodologically, resources from the theory of reception and the hermeneutics of the history to interpret the documents (poems) were used in order to appreciate the discursive articulation between text, reader and context. In conclusion, the extensive and intense poetic work of the exiles in the Dominican Republic was characterized for their political and social commitment, expression of uprooting and longing, and by their contribution to the revitalization of culture in the receiving country.